Heart rate variability during Hemodialysis in patients with chronic renal disease - Silva, Sidney Benedito (2015)
Background: Few studies evaluated cardiac autonomic responses induced by hemodialysis. We aimed to evaluate cardiac autonomic regulation during hemodialysis in haemodynamically stable patients with chronic renal disease. Method: Heart rate variability (HRV) was analyzed in the time and frequency domains in the following periods: Pre-dialysis (10 minutes before); Hemodialysis (240 minutes). Results: The standard deviation of all normal RR intervals (SDNN) increased 60-90min after hemodialysis compared to pre-hemodialysis (29.77±12ms vs. 51.70±41.6ms-p<0.05). The percentage of adjacent RR intervals with a difference of duration greater than 50ms (pNN50) also raised 180-210 min after hemodialysis compared to 0-30 min after hemodialysis (1.29±3.5 vs. 4.37±7.8-p<0.05). Low frequency (LF) (ms2) increased 150-180 min after hemodialysis compared to pre-hemodialysis (168.2±179.8 ms2 vs. 562.6±455.7 ms2: p<0.05) and high frequency (HF) (ms2) band raised 150-180min and 180-210 after hemodialysis compared to pre-hemodialysis (59.3±70.78 ms2 vs. 212.5±304.9 ms2 vs. 186.3±335.1 ms2: p<0.05). Conclusion: Hemodialysis acutely increased HRV, raising the parasympathetic component of HRV.